Predictability of the Profit Post Revision of Financial Accounting Based on the Supply Chain Management: Empirical Study from Islamic Banks in Indonesia - Sri Wahyuni; Pujiharto Pujiharto; Zulfikar Zulfikar (International Journal of Supply Chain Management, 2020)
Abstract- Thuis paper investigates the impact of supply chain integration on organizational performance in Indonesian banking sector. For this purpose the earnings predictability of Islamic banks in Indonesia are examined by investigating earnings volatility and the factors that influence it. In particular: 1) to examine the volatility of Islamic bank earnings; 2) investigate the effect of earnings volatility on the discretion of Islamic bank managers in determining the fair value of credit / financing; and 3) examine the positive effect of the allowance for possible losses on earning assets on the income smoothing of Islamic banks. This research is a quantitative study with the object of Islamic commercial banks in Indonesia with a research period of 2013-2016. The data used in the form of secondary data that is annual BUS report and then analyzed using multiple linear regression. The analysis shows that: 1) There is earnings volatility in Islamic banks after the revision of PSAK 50/55; 2) Earnings volatility does not affect managers' discretion in determining the fair value of financing; 3) Allowance for possible losses on earning assets has no positive effect on the income smoothing of Islamic banks; 4) Self-assessment of corporate governance can reduce the income smoothing of Islamic banks. The results of this study provide significant contributions to managers of Islamic banks, Bank of Indonesia, and Badan Penyusun Standar Akuntansi Keuangan Syariah that revised PSAK 50/55 causes volatility of earnings generated, but in Islamic banks, volatility does not cause manager discretion in determining the fair value of financing, like a conventional bank.